Nonlinear finite element modeling and parametric analysis for the design implication of expanded rib steel bars in RC beams - Tabish Ali; Robin Eunju Kim; Kun-Soo Kim; Ki-Tae Park (Developments in the Built Environment, 2023)
The quest for innovative design of reinforced-concrete to make it more durable, flexible, and sustainable has brought a transition from traditional methods of lap splicing to the use of anchor-head bars. One such innovation is the state-of-the-art Expanded Rib Steel Bar (ERSB) technique which reduces the conventional splice-length and also lessens the stress concentration at the concrete anchor-head contact areas to avoid brittle failure. Leveraging the four-point-bending experimental results of ERSB and two conventional designs, this paper investigates the performance of ERSB using a nonlinear 3D-Finite-Element Model. The results indicate that the proposed FEM reproduces the experimental behavior of ERSB in terms of maximum strength, displacement, ductility ratio, and crack pattern accurately. Moreover, the performance of ERSB is superior than the single-head-anchor bars and similar to that of the reinforced beams without joints. A parametric study then suggests design implications which can be adopted to develop guidelines for designing ERSBs.